Coping with burnout and the impact of the COVID-19 pandemic on workers’ mental health: A systematic review - Rossi, Maria Francesca; Gualano, Maria Rosaria; Magnavita, Nicola; Moscato, Umberto; Santoro, Paolo Emilio; Borrelli, Ivan (Frontiers in Psychiatry, 2023)
Introduction The COVID-19 pandemic had a negative impact on the psychological wellbeing of workers worldwide. Certain coping styles may increase burnout risk. To investigate the relationship between burnout and coping styles, a systematic review was performed. Methods Following the PRISMA statements, three databases were screened up until October 2022, including research articles written in English language and investigating the relationship between burnout and coping strategies in workers. The quality of articles was assessed by the Newcastle-Ottawa Scale. Results The initial search resulted in 3,413 records, 15 of which were included in this review. Most studies were performed on healthcare workers (n = 13, 86.6%) and included a majority of female workers (n = 13, 86.7%). The most used burnout assessment questionnaire was the Maslach Burnout Inventory (n = 8, 53.3%), and the most used coping assessment tool was the Brief-COPE (n = 6, 40.0%). Task-related coping was a protective factor for burnout in all four studies investigating its correlation with burnout dimensions. Two of the four studies investigating emotion-oriented coping found that it was protective while the other two found that it was predictive of burnout. All five studies investigating avoidance-oriented coping and burnout dimensions found that this coping style was predictive of burnout. Discussion Task-oriented and adaptive coping were protective for burnout, avoidance-oriented, and maladaptive coping were predictive factors of burnout. Mixed results were highlighted concerning emotion-oriented coping, suggesting that different outcomes of this coping style may depend on gender, with women relying more on it than men. In conclusion, further research is needed to investigate the effect of coping styles in individuals, and how these correlates with their unique characteristics. Training workers about appropriate coping styles to adopt may be essential to enact prevention strategies to reduce burnout incidence in workers.